Cauliflower‐Like Hierarchical Porous Nickel/Nickel Ferrite/Carbon Composite as Superior Bifunctional Catalyst for Lithium‐Air Battery. Issue 12 (24th March 2020) - Athika, Mattath; Devi, Vaithiyanathan Sankar; Elumalai, Perumal
Abstract: Rational design of cost‐effective oxygen electrode catalysts for metal‐air batteries is indispensable for developing next‐generation energy storage devices especially to use in electric vehicles. In this work, non‐precious Nickel/Nickel Ferrite on carbon matrix (NNFOC) nanocomposite as bifunctional air‐breathing electrode for rechargeable Li‐air battery is proposed. The NNFOC composite on rotating ring disc electrode (RRDE) exhibited good oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) activities. The synergistic contribution from Ni, nickel ferrite and porous carbon network that resulted more reaction sites, high conductivity and fast diffusion pathways, lead to enhanced ORR and OER activities. The CR‐2032 coin‐type and conventional split cell Li‐air battery were fabricated using the NNFOC composite as air‐breathing oxygen electrode and lithium metal as anode. The open‐circuit voltage of the coin cell was invariant for more than 5 days, while the split cell exhibited high discharge capacity of 3820 mAh g ‐1 at a current density of 50 mA g ‐1 . The charged split cell could power a commercial 2.8 V LED bulb for more than 5 h continuously. Abstract : The simple solution combustion synthesized nickel/nickel ferrite/carbon (NNFOC) nanocomposite as a bifunctional electrocatalyst towards oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) was examined. The fabricated split cell Li‐air battery exhibited high discharge capacity of 3820 mAh g −1 at a high current density of 50 mA g −1 . The charged split cell could power a commercial 2.8 V LED bulb for more than 5 h continuously.